Pengembangan dan Penerapan SMS Broadcast sebagai Media Penyaluran Informasi pada SD Negeri 1 Besakih - I Gusti Ayu Desi Saryanti; Rosalia Hadi; Riza Wulandari; Ni Luh Gede Pivin Suwirmayanti; Nyoman Ayu Nila Dewi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Mass SMS or the term generally called SMS Broadcast is a method of sending SMS to many numbers from one source or server with the same message content. Given its one-way nature, this type of SMS is very suitable to be used as a form of monitoring such as providing information to related parties. Partners in this activity are teachers or admins who record information to students or parents related to everything from the school. The location of internal service at this time is SD Negeri 1 Besakih. At this time there are still obstacles in the delivery of information as well as the use that is used to remember the location of this school is in the disaster-prone area (KRB) of Mount Agung which at any time can cause the learning process to stop or the temporary location of teaching and learning to be moved. Based on the problems faced, training on the use of SMS Broadcast for teachers or school administrators was carried out which aims to facilitate and convey information to parents of students. For this reason, it is carried out in stages starting with socialization, and training on the application of SMS Broadcast.